RANCANG BANGUN WEBSITE PENYEWAAN STUDIO FOTO RUANG BOHO DENGAN FRAMEWORK LARAVEL - Anisah Cahya Isvara (2022)
The photo studio rental information system (case study of the Boho Ruang Photo Studio) is a system that provides information regarding the rental and checking of the Boho Room photo studio schedule. The goal is to make it easier for every business person or actor involved in the rental process, schedule checks, transaction data recaps, and rental reports within a certain time frame. Boho Room has 4 choices of studio rooms, namely Boho Room, Boho Terrace, Boho Room, or a formal studio without a theme, namely Boho Studio. With several choices of rooms at the Ruang Boho studio, the rental method will be more complex. In the current system, the rental of the Boho Room photo studio is recorded through the WhatsApp platform and rewritten in Microsoft Excel so that human errors are possible. The method used in system analysis is PIECES and the method used in software development. This system uses the Laravel framework and Bootstrap CSS and for the database uses MySql. With this method, a website-based information system is produced that produces features for rentals and schedule checks that make it easier for studio managers and customers.